Strength and speed characteristics of elite, subelite, and recreational young soccer players - Gissis, I.; Papadopoulos, C.; Kalapotharakos, V. I.; Sotiropoulos, A.; Komsis, G.; Manolopoulos, E. (Research in Sports Medicine, 2006)
The purpose of the present study was to compare maximal isometric force, force-time curve characteristics, pedaling rate, vertical jump, and sprint performance among young soccer players from different competition levels. Fifty-four (54) young soccer players were divided into three groups according to competition level: the elite group (n = 18) consisted of soccer players from the national youth soccer team of Greece, the subelite group (n = 18) consisted of youth soccer players who participated in the local championship, and the recreational group (n = 18) consisted of recreational soccer players. All groups were evaluated for maximal isometric force, explosive force at 100 msec, peak force relative to body mass, rate of force development, squat and drop jump heights, 10 m sprint time, and pedaling rate. The elite group presented significantly (p < 0.05) higher maximal isometric force, vertical jump height, and pedaling rate, and lower 10 m sprint time in comparison with the subelite and recreational groups. No significant differences were observed in strength and speed characteristics between the subelite and recreational young soccer players. The findings of the present study suggest that the elite young soccer players can be distinguished from subelite and recreational young soccer players in strength and speed characteristics. These strength and speed measures can be used for strength and speed diagnosis, and for designing and evaluating training programs.